Development of a 3-Dimensional Prognostic Score for Patients With Symptomatic Peripheral Artery Disease: PAD3D Score. (August 2020) - Dopheide, Jörn F.; Ramadani, Hana; Adam, Luise; Gahl, Brigitta; Papac, Lucija; Veit, Jonas; Kaspar, Mathias; Schindewolf, Marc; Baumgartner, Iris; Drexel, Heinz
Peripheral artery disease (PAD) is a high-risk condition for cardiovascular (CV) events, but no specific prognosis assessment tool exists. We developed an individual risk score (PAD 3D ) based on the combined predictive value for mortality, including (1) age, (2) severity of PAD, and (3) extent of atherosclerosis. Patients (n = 1310) with symptomatic PAD were followed up for a mean of 50 ± 26 months. The cohort was randomly subdivided into a test and validation cohort. All-cause and CV mortality were prospectively analyzed for PAD 3D score and in combination with classical risk factors. For the test and validation cohort (n = 655 each), all-cause and CV mortality were predicted ( P < .001) by the PAD 3D score. Additional inclusion of classical risk factors did not increase discrimination compared with PAD 3D as "area under receiver-operating characteristic" curves were similar for both scores at any time point. Thus, the addition of the classical risk factors to PAD 3D did not further improve the prognostic value. The PAD 3D score provides a risk gradient of a 4.5-fold increase in all-cause and CV mortality. We developed a score for precise prediction of all-cause and CV mortality. The PAD 3D score promises to allow for personalized goals in risk intervention.